2016
DOI: 10.1089/zeb.2016.1274
|View full text |Cite
|
Sign up to set email alerts
|

Use of Coronary Ultrasound Imaging to Evaluate Ventricular Function in Adult Zebrafish

Abstract: So far, imaging of the adult zebrafish heart and assessment of heart failure in adult zebrafish have been very limited. Here, we describe a new method for in vivo imaging of the hypertrabeculated heart of the adult zebrafish using miniaturized cardiac ultrasound catheters obtained from the cardiac catheterization laboratory. This method allows the observation of the ventricle of zebrafish and the assessment of ventricular diameters during diastole and systole, as well as heart rate and fractional shortening. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Although the use of high frequency echocardiography in zebrafish has recently begun to be explored, there is a critical lack of standardized approaches for image acquisition and data analysis. Studies to date ( ) ( Ernens et al, 2016 ; González-Rosa et al, 2014 ; Hein et al, 2015 ; Ho et al, 2002 ; Huang et al, 2015 ; Kang et al, 2015 ; Lee et al, 2014 , 2016 ; Parente et al, 2013 ; Sun et al, 2008 , 2015 ; Wilson et al, 2015 ) have displayed substantial differences in methodology, including scanning environment (room air versus underwater), choice and concentration of anesthetic agent, scanning views and analysis techniques, and fish age, sex and background strain, with limited data on quality control and reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of high frequency echocardiography in zebrafish has recently begun to be explored, there is a critical lack of standardized approaches for image acquisition and data analysis. Studies to date ( ) ( Ernens et al, 2016 ; González-Rosa et al, 2014 ; Hein et al, 2015 ; Ho et al, 2002 ; Huang et al, 2015 ; Kang et al, 2015 ; Lee et al, 2014 , 2016 ; Parente et al, 2013 ; Sun et al, 2008 , 2015 ; Wilson et al, 2015 ) have displayed substantial differences in methodology, including scanning environment (room air versus underwater), choice and concentration of anesthetic agent, scanning views and analysis techniques, and fish age, sex and background strain, with limited data on quality control and reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…1 In their recent article, Ernens et al reported that similar responses to anemia occur in the zebrafish heart. 2 We note with interest that Ernens et al found that heart rate was depressed, in contrast to the relative tachycardia that is usually present in anemia-associated human heart failure. 1 These findings raise a thought-provoking conundrum regarding the cause of bradycardia and its impact on cardiac function in this zebrafish model.…”
mentioning
confidence: 92%
“…Anesthetic agents and temperature are known to influence heart rate during echocardiography, 5,6 and Ernens et al suggested that the dose of anesthetic used (tricaine methane-sulfonate, 160 mg/L), and/or the performance of their studies at room temperature, may have contributed to their heart rate results. 2 These factors would apply equally to wildtype and anemic fish, however, and thus do not explain the observed differences between groups. 2 A parsimonious explanation is that anemic zebrafish have a substantially greater susceptibility than healthy zebrafish to cardiodepressant effects of anesthesia.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, researchers have adapted light-sheet microscopy (Packard et al, 2017), MRI (Koth et al, 2017;Merrifield et al, 2017) and microcomputed tomography (µ-CT) (Descamps et al, 2014;Weinhardt et al, 2018;Ding et al, 2019) to define the morphology of zebrafish organs. Others have used echocardiography to characterize the functional impact of cardiac disease and regeneration in adult zebrafish (Ho et al, 2002;Sun et al, 2008;Parente et al, 2013;González-Rosa et al, 2014;Hein et al, 2015;Huang et al, 2015;Wilson et al, 2015;Ernens et al, 2016;Lee et al, 2016;Wang et al, 2017;Benslimane et al, 2019). However, a systematic workflow to study cardiac phenomics in adult zebrafish has yet to emerge.…”
Section: Introductionmentioning
confidence: 99%